Assessing the efficacy and safety of Yinqiao powder-maxing Ganshi decoction in the treatment of the major symptoms of mild and moderate COVID-19 by telemedicine-study protocol for a randomized, double-blind, placebo-controlled trial - Chi Him Sum; Tong Wendy Li; Hongwei Zhang; Hongwei Zhang; Hing Yu Hung; Ben Yuk Fai Fong; Ben Yuk Fai Fong; Wai Ling Lin; Tak Yee Chow; Ka Chun Leung; Cho Wing Lo; Chon Pin Chia; et al. (Frontiers Media S.A., 2024)
Background: The Coronavirus disease 2019 (COVID-19) is the largest global epidemic in recent time. Chinese medicine has been recognized by the World Health Organization as an effective treatment for COVID-19, but there is still a lack of high-quality randomized, double-blind trials using placebo as the control to support its application, which may hinder its further promotion locally and internationally.Objectives: This study will evaluate the efficacy and safety of Yinqiao Powder-Maxing Ganshi Decoction with variation in relieving major symptoms of mild and moderate COVID-19 by telemedicine.Methods and design: This clinical study is a randomized, double-blind, placebo-controlled trial that applies telemedicine to evaluate the efficacy and safety of Yinqiao Powder-Maxing Ganshi Decoction in the treatment of mild and moderate COVID-19. Eligible subjects will be randomly divided into either treatment or placebo groups for up to 14 days after stratification according to age (A:18-49, B:50-65) and the number of vaccinations (a: ≥3 doses, b: ≤2 doses). The treatment group will receive Yinqiao Powder-Maxing Ganshi Decoction granules along with certain variation based on their symptoms, and the placebo group will receive the same amount of placebo granules. Subjects will be prescribed different additions based on their symptoms and pathogenesis at the inclusion. The oral temperature, oximeter, result of rapid antigen test and symptom score will be recorded by subjects until they have stopped the medication. Subjects are required to have follow-up assessment by video-conference on days 7, 14 and 35. The time for the body temperature returning to normal will be used as the primary outcome.Discussion: This trial will provide scientific evidence on the use of Yinqiao Powder-Maxing Ganshi Decoction for the treatment of COVID-19, and the results would help raise the awareness in Hong Kong and the international community on the use of Chinese herbal medicine for treating COVID-19.Clinical Trial Registration:clinicaltrials.gov, identifier NCT05787327.